IMPLEMENTASI PROGRAM SEMBAKO MURAH BERSUBSIDI DI KABUPATEN BENGKALIS - Asra, Yunelly; Maulana, Hutomo Atman (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the public's perception of the price of basic staple goods in Bengkalis Regency, the commodities needed by the community and the ability of the community to buy. The research method is quantitative descriptive research. Data collection techniques used surveys, observational and In Deph Interviews. Data analysis used associative descriptive technique. The research variables are the amount of price, commodity, the ability of the community and the method of distributing subsidized low-cost basic food packages. Data collection was carried out by means of probability sampling with Stratified random sampling of 1000 respondents in 11 (eleven) sub-districts of Bengkalis Regency. The results indicate that the prices for staple goods at traditional markets in Bengkalis Regency are not the same as the basic prices set by the government because they are influenced by geographical conditions, causing differences in transportation costs. The commodities needed by the community in subsidized low-cost basic basic food packages are rice, sugar, cooking oil, eggs and milk. The ability of the people of Bengkalis Regency to purchase is in the price range of Rp. 25,000 to Rp. 50,000.